Traditional uses of fire in the Ayacucho parish, Santa Ana Canton, Manabí province, Ecuador - Ramos-Rodríguez, Marcos Pedro (2021)
The use of fire by agricultural producers is a common practice that has been used since immemorial times in most countries of the world. The objective of this work was: a) to diagnose the traditional uses of fire in the Ayacucho Parish, Santa Ana Canton, Manabí province, Ecuador, b) to verify the farmers perception  about the benefits and negative effects of fire, c) to identify  prevention measures to use fire and how they proceed when they have to fight an unwanted fire, and d) specify their participation in training sessions on the use of fire and forest fires. The information that forms the diagnosis was obtained by applying a semi-structured survey with open and closed questions to 150 rural producers from February to May 2019. Statistical analysis was performed with SPSS Statistics for Windows (Version 22.0). The results showed that the use of fire in the community is common, burning on specific dates every year, although November was the month most frequently mentioned, the average burned area being 1.30 ha. The most important purpose of using fire in the locality is cleaning the land for sowing or planting. The χ2 test showed that there is no statistically significant association between variables that describe the characteristics of the producers and those of the use of fire. The work allowed obtaining important and relevant information on the use of fire in the Ayacucho Parish, which may be used by decision-makers of fire management activities.